(untitled) (Karya Ilmiah Mahasiswa (KIMA), 2024)
The study aimed to examine the difficulties of students with special needs in learning English. The research method used is descriptive qualitative, which gave descriptive of the activity of students with special needs and their learning difficulties. The sample of this study was students with special needs at the senior high school in one of SLB Makassar consisting a mental retarded student and two autistic students. The results showed that the difficulties of students with special needs in learning English are difficulties in understanding and difficulties in solving problems. Furthermore, it was found that listening as the most challenging skills. Those is caused by classroom instructional activities, learning interest, learning motivation and family environment.